Consistent practice for pressure ulcer prevention in long-term older people care: A quasi-experimental intervention study - Mäki-Turja-Rostedt S; Leino-Kilpi H; Korhonen T; Vahlberg T; Haavisto E (Wiley, 2025)
Background Consistent practice, an agreed clinical practice based on evidence, has been considered as a base for effective provision of quality and safety of care. As a result, patients have an equal quality of care regardless of the organisation or worker. However, despite the international guidelines, pressure ulcer prevention practices vary in long-term older people care.Aim To develop, implement and evaluate the impact of renewed, consistent practice for pressure ulcer prevention, in long-term older people care.Design A quasi-experimental intervention study.Methods Two long-term older people care facilities chosen with convenience sampling were randomly allocated to intervention or comparison group. Registered and practical nurses, in total 141/112, participated in the study. The renewed consistent practice based on international guidelines for pressure ulcer prevention was developed and implemented using the Operational Model for Evidence-Based Practices (OMEBP). Frequencies and agreement of PU prevention practices in line with international guidelines in the care facilities were measured using the PUPreP instrument.Results In the intervention facility, improvement in line with international guidelines was seen in the frequency of PU prevention practices in risk assessment, nutrition, pressure-relieving devices and documentation. Furthermore, improvement was seen in the intervention facility in all six areas of agreement on practices.Conclusions The results of this study support the implementation of PU prevention guidelines in long-term older people care (LOPC) and more widely in healthcare settings for older people to promote consistent practice, and safety and equal quality of care.